CORRELATION OF HEARING IMPAIRMENT WITH DESFERAL AND SERUM FERRITIN LEVEL IN β THALASSEMIA MAJOR PATIENTS - K Kiakojouri, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: In β thalassemia major that begins in the first year of life, iron deposition after blood transfusion is undesired event that must be removed with iron chelators such as desferal. On the other hand, it is not collected information about the hearing impairment in the patients who received desferal therapy The aim of this study was to assess the presence and absence of hearing impairment in β thalassemia major patients and its correlation with desferal and ferritin level.METHODS: This analytical study was performed on 100 thalassemic patients in Amirkola thalassemic center. Fifty patients had received regular desferal therapy (case group) and fifty patients had received irregular desferal therapy (control group). Age, sex, ferritin level, route of desferal therapy and educational level had been recorded for both groups. They have been evaluated for auditory quality with tympanometer and audiometer.FINDINGS: In the case group four patients (8%) and in control group eight patients (16%) had conductive hearing loss. It was not meaningful difference. Also in the two groups there were no meaningful correlation between ferritin level and hearing loss. Tympanometry had shown some disturbance in both groups seven patients (14%) and fifteen patients (30%) in case and control groups, respectively (p=0.029).CONCLUSION: The results of this study showed that adequate regular desferal therapy in β thalassemia major patients is not associated with hearing impairment.